Mengungkap Identitas Pelaku Pelecehan Seksual di Media Sosial Melanggar UU Perlindungan Data Pribadi? - Widya Kusvie Ayuningtyas; Tri Nastiya; Fauziah Lubis (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
The purpose of this research is to examine whether disclosing the identity of perpetrators of sexual harassment on social media violates the Personal Data Protection Act? Because according to the 2021 Komnas Perempuan Annual Records, sexual violence against women has increased significantly over the last ten years (2010-2020). The occurrence of sexual violence is caused by several factors which will be discussed in this paper. The formulation of the problem taken in this research is whether the victim who reveals the identity of the perpetrator of sexual harassment on social media violates the Personal Data Protection Law and what legal remedies can be taken by victims of sexual harassment and what are the appropriate sanctions for perpetrators of sexual harassment. The research method is a descriptive method, namely by explaining the results of research in an accurate, systematic and accurate manner. The result of this research is that personal data protection is one of human rights which is part of personal self-protection. Based on the Personal Data Protection Law, it is concluded that victims of sexual harassment who reveal the identity of the perpetrator have the potential to be subject to articles that have been approved by the Indonesian state. Legal remedies for victims of sexual harassment who reveal the identity of the perpetrator is to make a report to the police that they have experienced sexual harassment, if the victim feels afraid it can be reported by someone who knows the incident, sexual harassment can also be reported by the UPTD PPA and during the process of reporting to the police the victim entitled to guaranteed protection from the LPSK and several kinds of sanctions with the type of case of perpetrators of sexual harassment will also be attached to this paper Keywords: Sexual Harassment, Personal Data Protection Law, Social Media